2013
DOI: 10.1002/iub.1172
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiac autophagy by insulin‐like growth factor 1

Abstract: Insulin-like growth factor-1 (IGF-1) signaling is a key pathway in the control of cell growth and survival. Three critical nodes in the IGF-1 signaling pathway have been described in cardiomyocytes: protein kinase Akt/mammalian target of rapamycin (mTOR), Ras/Raf/extracellular signal-regulated kinase (ERK), and phospholipase C (PLC)/inositol 1,4,5-triphosphate (InsP 3 )/ Ca 21 . The Akt/mTOR and Ras/Raf/ERK signaling arms govern survival in the settings of cardiac stress and hypertrophic growth. By contrast, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…As a critical player in the nodal point of multiple signaling pathways, the protein kinase Akt responds to multiple upstream signals and regulates important cellular processes such as cell proliferation, energy metabolism, and autophagy (Troncoso et al 2013;Yao et al 2014). One of the most well-defined downstream targets of Akt is mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…As a critical player in the nodal point of multiple signaling pathways, the protein kinase Akt responds to multiple upstream signals and regulates important cellular processes such as cell proliferation, energy metabolism, and autophagy (Troncoso et al 2013;Yao et al 2014). One of the most well-defined downstream targets of Akt is mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy can be regulated by several different energy sensing stimuli: the availability of AAs in a cell regulates mTOR activity; the glucose level in blood regulates release of insulin and glucagon which have opposing effects on autophagy; and conditions such as metabolic syndrome and caloric restriction regulate autophagy and mitophagy. Insulin suppresses macroautophagy by activating the phosphatidyl-inositol triphosphate (PIP 3 ) cascade leading to phosphorylation and activation of Akt and subsequently mTOR, which inhibits autophagy [122]. Usually high insulin is followed by an increase in AAs in the cytosol, which also activates mTOR, reinforcing the same pathway.…”
Section: Mitochondrial Turnover In the Context Of The Organ And Thmentioning
confidence: 99%
“…This effect also emerges as a therapeutic target of clinical relevance on CV biology [43]. Recently, Troncoso et al showed that IGF-1 negatively modulates nutrient deprivationinduced cardiac autophagy involving activation of the Akt/mTOR and AMPK/mTOR signaling pathways, which in turn promoted the mitochondrial activity [44,45]. Despite the apparent physiological association between IGF-1 and insulin axis they activate differentially the Akt1 and Akt2 isoforms, respectively.…”
Section: Igf-1r Signaling Pathwaysmentioning
confidence: 93%
“…Akt1 is associated with normal cardiac growth, whereas Akt2 is linked to cardiomyocyte survival and metabolism [46]. Interestingly, both insulin and IGF-1 increase the mitochondrial activity in cultured rat cardiomyocytes [45,47] raising new questions regarding the complex interplay between their downstream signaling pathways. In this context, the manipulation of the ratio IGF-1R/IR affects hybrid receptor formation and insulin sensitivity in endothelial cells [48,49].…”
Section: Igf-1r Signaling Pathwaysmentioning
confidence: 98%